Young Adult Literature: Rite of Passage or Rite of Its Own - Katherine Proukou (The ALAN Review, 2005)
Myths swirl about young adult (YA) literature, from Huckleberry Finn to Harry Potter: It’s literature for teenagers; it’s literature about teenagers; it’s stylistic and simplified literature; it’s overly didactic and, of course, shorter than a real novel. It is a rite of passage. But it is much more. It is about life, its histories and potentialities, transformations and choices; it is about conflicts between the claim of the individual and the claims of culture (Freud); it is about life’s fantastic flux of being. It is about new beginnings and other directions; of young heroes who wind upthreads and carry wisdom, of the child-one who sees, clearly, that the emperor has no clothes. It is not only about rites of passage, but is also a rite of its own, an archetypal icon-bearer of the monomyths that recreate us, as an examination of Huckleberry Finn, The Chocolate War and Shabanu: Daughter of the Wind, three very different novels spread out over time, illustrate.
Keywords: adolescence